Flavors of Rizal promoting Rizal's culinary tourism through a "farm-to-table" Food Community Complex in Binangonan, Rizal - Ambrocio, Lance David B. (College of Architecture, University of the Philippines Diliman, 2017)
This thesis is about creating a space to promote Rizal's gastronomic treasures and its growing culinary tourism through the establishment of a food community complex. Creating a framework based on the theories of terroir, cultural capital, and sustainable food tourism, the author has idenified three important aspects: environmental, economical, and socio-cultural sustainability in terms of culinary tourism. A site, chosen based upon a selection criteria that takes advantage of a site's location, gastronomic potential, accessibility conditions, availability of basic services, accessible to agricultural and fisheries producers, the support of the local government, infrastructure, and transport and communication facilities, wll be designed and developed to highlight Rizal's culinary products and unique food preparation methods. The landscape design will highlight the application of the "farm-to-table" approach and rekindle interest on Rizal's renowned local delicacies. Keywords: culinary tourism, cultural, farm-to-table, food community complex, local delicacies